2017
DOI: 10.1136/bmjopen-2016-015025
|View full text |Cite
|
Sign up to set email alerts
|

Are there patient-related factors that influence sickness certification in patients with severe subjective health complaints? A cross-sectional exploratory study from different European countries

Abstract: ObjectivesTo develop hypotheses about whether there are patient-related factors that influence physicians’ decision-making that can explain why some patients with severe subjective health complaints (SHCs) are more likely to be granted sick leave than others.DesignExploratory cross-sectional.SettingAssessments of patient-related factors after watching nine authentic video recordings of patients with severe SHC from a Norwegian general practice. Our previous study showed that three of these nine patients were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Previously, it has been pointed out that there is a need for international comparisons of similar interventions in different countries, as a knowledge base for actions regarding physicians’ sickness certification practice [ 9 , 62 ]; this need is still not met.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been pointed out that there is a need for international comparisons of similar interventions in different countries, as a knowledge base for actions regarding physicians’ sickness certification practice [ 9 , 62 ]; this need is still not met.…”
Section: Discussionmentioning
confidence: 99%
“…Many physicians perceive sick leave tasks as difficult6 and time-demanding 7. Moreover, they experience problems in assessing the patient’s ability to work,2 8 such as for patients suffering from subjective and composite health complaints,9 10 and disagreements or conflicts with patients,11 especially when the GP denies a patient’s request 12. There is also a moral hazard that individuals request sickness leave more than necessary 13…”
Section: Introductionmentioning
confidence: 99%
“…A Swedish focus group interview study showed that GPs and GP trainees were positive to include other healthcare professionals in the patient's rehabilitation process [14]. Still, the patients are the prime sources of information about themselves as emphasized in a study where recorded dialogues between patients and physicians were assessed by GPs from different European countries [15].…”
Section: Introductionmentioning
confidence: 99%